2014
DOI: 10.1371/journal.pone.0099168
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into 1-Aminocyclopropane-1-Carboxylate (ACC) Deaminase Phylogeny, Evolution and Ecological Significance

Abstract: The main objective of this work is the study of the phylogeny, evolution and ecological importance of the enzyme 1-aminocyclopropane-1-carboxylate (ACC) deaminase, the activity of which represents one of the most important and studied mechanisms used by plant growth–promoting microorganisms. The ACC deaminase gene and its regulatory elements presence in completely sequenced organisms was verified by multiple searches in diverse databases, and based on the data obtained a comprehensive analysis was conducted. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
176
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 217 publications
(187 citation statements)
references
References 105 publications
9
176
0
2
Order By: Relevance
“…Characterization of this enzyme effects on stress management is observed for the past two decades, and now considered as a key phenomenon of PGP traits (Glick 1995). Many of the actinobacteria are shown to produce ACC deaminase such as Streptomyces, Amycolatopsis, Nocardia, Mycobacterium, Rhodococcus, and others (Nascimento et al 2014). Siddikee et al (2010) isolated several halotolerant actinobacteria strains with ACC deaminase, from the soil of barren fields and the rhizosphere of naturally growing halophytic plants and found that they can increase canola plant growth.…”
Section: Pgp Actinobacteria As Stress Relieversmentioning
confidence: 99%
“…Characterization of this enzyme effects on stress management is observed for the past two decades, and now considered as a key phenomenon of PGP traits (Glick 1995). Many of the actinobacteria are shown to produce ACC deaminase such as Streptomyces, Amycolatopsis, Nocardia, Mycobacterium, Rhodococcus, and others (Nascimento et al 2014). Siddikee et al (2010) isolated several halotolerant actinobacteria strains with ACC deaminase, from the soil of barren fields and the rhizosphere of naturally growing halophytic plants and found that they can increase canola plant growth.…”
Section: Pgp Actinobacteria As Stress Relieversmentioning
confidence: 99%
“…A complete description of the phylogeny and evolution of the genes encoding acdS and its major regulatory gene, acdR, has been recently elaborated (Bruto et al, 2014;Nascimento et al, 2014). Information regarding acdS/acdR sequences must be considered together with the habitat, the origin, and the enzymatic activity of completely sequenced bacterial strains to obtain a comprehensive view.…”
Section: Distribution and Phylogeny Of Acc Deaminasementioning
confidence: 99%
“…Thus, microorganisms that can produce IAA and utilize ACC may have a competitive advantage over other soil microorganisms (Glick et al, 1998, Stearns et al, 2012. It is know that ACCD modulates ACC metabolism and is related to plant growth promotion and microorganism's developmental processes (Nascimento et al, 2014) and thus protecting the plant from stress (Subramanian et al, 2015).…”
Section: Stress (Salt and Ph) Tolerant Pgprmentioning
confidence: 99%
“…Additionally, recent results suggest a considerable degree of horizontal ACCD gene transfer events (Nascimento et al, 2014). Hence, exploration of more ACCD gene from diverse bacterial sources and in depth understanding of the function of this enzyme especially in plant physiology signifies its importance.…”
Section: Stress (Salt and Ph) Tolerant Pgprmentioning
confidence: 99%
See 1 more Smart Citation